HAKIKAT MITOLOGI SEBAGAI PERKEMBANGAN AGAMA AWAL HINGGA MASA KINI - Etikasari, Etikasari (Studia Sosia Religia, 2025)
The essence of natural power is in humans in their time. The higher the human intellect, the higher the values taught to the next generation. This study aims to re-examine primitive religions that can now be abandoned, and how humans would be without nature to protect. The methodology of this study focuses on library research and podsat media about myths is the earth's word as the balance of humans on earth and nature. The results of this study show that myths are a way of understanding spiritual values, human communication with nature and as a door to understanding the philosophy of life.